2017
DOI: 10.1371/journal.pone.0189727
|View full text |Cite
|
Sign up to set email alerts
|

Altered cerebral hemodyamics and cortical thinning in asymptomatic carotid artery stenosis

Abstract: Cortical thinning is a potentially important biomarker, but the pathophysiology in cerebrovascular disease is unknown. We investigated the association between regional cortical blood flow and regional cortical thickness in patients with asymptomatic unilateral high-grade internal carotid artery disease without stroke. Twenty-nine patients underwent high resolution anatomical and single-delay, pseudocontinuous arterial spin labeling magnetic resonance imaging with partial volume correction to assess gray matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 57 publications
3
45
1
1
Order By: Relevance
“…These investigators also showed a linear correlation between lower flow and cortical thinning, a marker also associated with cognitive impairment [25,26]. This correlation was also demonstrated in patients with carotid disease [27].…”
Section: Discussion/conclusionmentioning
confidence: 68%
“…These investigators also showed a linear correlation between lower flow and cortical thinning, a marker also associated with cognitive impairment [25,26]. This correlation was also demonstrated in patients with carotid disease [27].…”
Section: Discussion/conclusionmentioning
confidence: 68%
“…Interestingly, paradoxically increased CBFs in the high convexity of the frontal and parietal regions were observed in the INPH group in comparison to the control group 57 . Furthermore, cerebral hypoperfusion has been considered as a predictor variable for cortical thinning 58 . In this study, SCCA revealed unique relationships between lateral ventricular enlargement and cortical thinning in INPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…For asymptomatic carotid stenosis, data on cortical thickness is scarce. A pilot study suggested, that altered cerebral perfusion in carotid stenosis is associated with regional cortical thinning [12]. Another study revealed a decrease of cortical thickness specifically in the anterior cerebral artery territory [13].…”
Section: Introductionmentioning
confidence: 99%